Pelvic Intravenous Leiomyomatosis - Case Report - Patricia Correia; Ana Castro; Anabela Rocha; Daniela Freitas; Cátia Carnide; Osvaldo Moutinho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Introduction Intravenous leiomyomatosis is a benign and rare condition that can result in cardiac events with fatal outcomes when left untreated. Intravenous leiomyomatosis is probably underestimated because the diagnosis is easily missed. We present a case of an intravenous leiomyomatosis without extra-pelvic involvement, with a brief review of this pathology. Case Report 46-year-old woman submitted to hysterectomy and bilateral adnexectomy because of a pelvic mass detected in ultrasound. During the surgery, intravenous leiomyomatosis diagnosis was suspected. Pathological analysis confirmed this suspicion. Further imaging exams were performed without detecting any anomalies related to this condition. The patient remained with no evidence of disease after one year of follow-up. Conclusion Intravenous leiomyomatosis is a rare condition that can lead to serious complications. Early diagnosis followed by an appropriate treatment is very important to patient outcome, and underdiagnoses can be counteracted if the gynecologist is aware of this entity.